In Whose Custody? – A Study of Culture in Crisis with Reference to the Novel and the Film - Singh, Astha (The Grove - Working Papers on English Studies, 2022)
In Custody is a novel by Anita Desai that studies the extinction of Urdu culture in post-partition India. The film adaptation of the novel has been done by Merchant Ivory Production in an attempt to not only convert the narrative from one art form to another, but also to use cinematic techniques to explore the socio-culture of India with the Urdu language being the central theme. This paper tries to explore the diminished Urdu culture and tries to analyze the question of its preservation in the modern world using technologies that have also been put forward in both art forms. The verses of Urdu poets and Faiz Ahmad Faiz used in the novel and in the film along with the progressive writers’ thought have also been dealt with. Hence, the theme of Urdu culture playing centrally, this paper studies various other aspects that have been presented in the film adaptation.